A review of the evidence for alternative and complementary medical approaches in the prevention of atherosclerotic cardiovascular disease and diabetes. Issue 1 (March 2017) - Nieves, Jonathan P.; Baum, Seth J.
Abstract : The use of complementary and alternative medicine approaches has increased in the recent years. It has been utilized in both the treatment and prevention of many chronic diseases, especially in the management of hypertension, diabetes, and hyperlipidemia. Lifestyle modifications play a fundamental role in alternative and complementary medicine. Regular exercise, maintenance of optimal weight, and a healthful diet play vital roles in maintaining ideal health. Specifically, the Dietary Approaches to Stop Hypertension and Mediterranean diets have been established as having beneficial effects on blood pressure and cholesterol and even cardiovascular outcomes. Still, additional supplements including fish oil, CoQ10, and red yeast rice (among others) have shown promising beneficial effects. Unfortunately, many of the beneficial claims of natural products are not scientifically proven, lack reproducibility, and/or yield conflicting results. Until more concrete evidence can be produced, it is important for physicians and patients alike to familiarize themselves with these natural products and increase their awareness of any potential adverse effects.